Identification of nine new susceptibility loci for endometrial cancer - Tracy A. O’Mara (Nature Portfolio, 2018)
Endometrial cancer is the most common invasive gynaecological cancer in developed countries. Here a meta-analysis identifies an additional nine novel endometrial cancer risk loci and eQTL analysis reveals risk variants associate with reduced expression of negative regulators of oncogenic signal transduction proteins.